2017
DOI: 10.1111/cas.13266
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism‐targeted therapy and withaferin A are effective for epidermal growth factor receptor tyrosine kinase inhibitor‐induced drug‐tolerant persisters

Abstract: In pathway‐targeted cancer drug therapies, the relatively rapid emergence of drug‐tolerant persisters (DTPs) substantially limits the overall therapeutic benefit. However, little is known about the roles of DTPs in drug resistance. In this study, we investigated the features of epidermal growth factor receptor–tyrosine kinase inhibitor‐induced DTPs and explored a new treatment strategy to overcome the emergence of these DTPs. We used two EGFR‐mutated lung adenocarcinoma cell lines, PC9 and II‐18. They were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…4 The expression of stem cell related markers such as oct3/4 and sox2, was high in cells with high expression of CD133, although we have not yet shown that CD133 directly plays a role on histological transformation. 4 Cancer senescence represents a state of cell cycle arrest. Upregulation of Bcl-2 is reportedly required for the initiation of cell senescence in mouse melanoma cells.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…4 The expression of stem cell related markers such as oct3/4 and sox2, was high in cells with high expression of CD133, although we have not yet shown that CD133 directly plays a role on histological transformation. 4 Cancer senescence represents a state of cell cycle arrest. Upregulation of Bcl-2 is reportedly required for the initiation of cell senescence in mouse melanoma cells.…”
Section: Discussionmentioning
confidence: 60%
“…Exposure to EGFR‐TKIs reportedly also lead to the emergence of drug‐tolerant cells that maintain variability, whereas the majority of the other cell populations typically die in EGFR ‐mutant NSCLC‐derived cell lines . We have previously shown that EGFR‐TKI‐induced drug‐tolerant persisters were composed of two types of cells, cancer stem‐like cells and senescent cells . The expression of stem cell related markers such as oct3/4 and sox2, was high in cells with high expression of CD133, although we have not yet shown that CD133 directly plays a role on histological transformation .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations